2020
DOI: 10.3390/ma13030676
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of the Flame Retardant Decorated Plywood Based on the Intumescent Flame Retardant Adhesive

Abstract: A novel type of flame-retardant decorated plywood (FDP) was designed and prepared based on one kind of intumescent flame-retardant adhesive. The flame-retardant adhesive was composed of the phosphorous-nitrogen flame retardant and melamine urea formaldehyde (MUF) resin. An adhesive was placed between the plywood substrate and the decorative veneer. The shear strength of the FDP satisfied the Class II (GB/T 9846) when the ratio of flame-retardant and MUF was less than 0.65. The thermal stability of the flame-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 33 publications
(35 reference statements)
0
7
0
1
Order By: Relevance
“…SEM images showed that the char surface of MIPU0 was continuous, dense, and fully expanded (Figure 8), and the internal pore size of the char was consistent and without damage (Figure 9). These indicated that MUF, APP, and PER cooperated well and formed an excellent swollen char during combustion [4,28]. When WPU was introduced into this system, the char surface was visibly discontinuous with poor gloss (Figure 6) and traces of shrinkage appeared, as well as holes (Figure 8).…”
Section: Morphology Of the Expanded Charmentioning
confidence: 93%
See 1 more Smart Citation
“…SEM images showed that the char surface of MIPU0 was continuous, dense, and fully expanded (Figure 8), and the internal pore size of the char was consistent and without damage (Figure 9). These indicated that MUF, APP, and PER cooperated well and formed an excellent swollen char during combustion [4,28]. When WPU was introduced into this system, the char surface was visibly discontinuous with poor gloss (Figure 6) and traces of shrinkage appeared, as well as holes (Figure 8).…”
Section: Morphology Of the Expanded Charmentioning
confidence: 93%
“…The MUF resin was synthesized with a molar ratio of formaldehyde/melamine and urea (F/(M + U)) of 1.30 [28]. A total of 40 g urea and 120 g formaldehyde solution were added to a three-necked flask, and the pH was set to 8.0-9.5 with 5% NaOH solution.…”
Section: Synthesis Of Melamine-urea-formaldehyde (Muf) Resinmentioning
confidence: 99%
“…However, most biomass-based carbon sources have not yet overcome the drawback of the need for a large number of intumescent flame retardants. In addition, they cannot yet eliminate the detrimental effects of flame retardants on the mechanical properties of wood materials [ 70 ]. To address the above issues, many researchers have attempted to incorporate silicon-containing compounds into biomass char sources to improve the thermal stability of biomass char sources and increase their compatibility with wood substrates, and preliminary results have been obtained [ 66 , 68 ].…”
Section: Composite Biological Intumescent Flame Retardantmentioning
confidence: 99%
“…The above-mentioned facts are easily lead to serious consequences of fire. [3,4] The fire hazard of plywood is able to be reduced by the flame retardant treatment of veneer and/or adhesive in the process of DOI: 10.1002/marc.202200018 plywood preparation by impregnation, coating, and addition. [5,6] Different nitrogen phosphorus flame retardants have been synthesized by chemical synthesis or physical doping with ammonium phosphate, urea, melamine, etc.…”
Section: Introductionmentioning
confidence: 99%